Large mineral and chemical companies and their reaction to calls of global economy - Ramanauskas, Julius; Sergeyev, Igor; Ponomarenko, Tatiana (Business: Theory and Practice, 2014)
The development of economy in terms of globalization, growth of innovative technologies provide changes in corporate strategies of the mining global companies. The research objective is to forecast export strategies of the head phosphate produ cers. Key results of the research: new regularities of the mineral resources markets were found out; approaches to management of companies was put forward; a forecast of the global phosphate market’s development was made; factors of manufacturing new and traditional types of product were found out.